2016
DOI: 10.1111/ped.12874
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell hepatitis with autoimmune hemolytic anemia in a Korean infant

Abstract: Giant cell hepatitis (GCH) with autoimmune hemolytic anemia (AHA) is a very rare disease characterized by early onset and severe clinical manifestations, including immune hemolytic anemia and hepatitis with cholestasis. The prognosis is poor despite aggressive immunosuppressive therapy. We report here the first case of GCH with AHA in East Asia. A 2-month-old boy was admitted with jaundice. Blood test indicated abnormal liver function and low hemoglobin. Direct Coombs test and several autoantibodies associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Interestingly, 36 h after PH, the only 1% of hepatocytes that were BrdU positive displayed an increased size, similar to hypertrophic hepatocytes observed at 4 weeks without PH (Figure 1C). Only few clinical cases of rare giant cell hepatitis described the existence of large cells in the liver after severe liver failure, 16 and one study of Raptor KO in the mouse liver, a critical mTORC1 component, has shown hypertrophic hepatocytes 17 . Hypertrophic cells in Reptin LKO display a hepatocyte morphology and are highly proliferative.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 36 h after PH, the only 1% of hepatocytes that were BrdU positive displayed an increased size, similar to hypertrophic hepatocytes observed at 4 weeks without PH (Figure 1C). Only few clinical cases of rare giant cell hepatitis described the existence of large cells in the liver after severe liver failure, 16 and one study of Raptor KO in the mouse liver, a critical mTORC1 component, has shown hypertrophic hepatocytes 17 . Hypertrophic cells in Reptin LKO display a hepatocyte morphology and are highly proliferative.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the cases have been described in Caucasian populations. However, very few cases from East Asia have also been reported [5].…”
Section: Discussionmentioning
confidence: 99%
“…4 Para el tratamiento, los inmunosupresores (prednisona y azatioprina) proporcionan una adecuada respuesta inicial en la mayoría de los pacientes; no obstante, pueden ocurrir recaídas. 5 Sin embargo, se considera que esta entidad es grave, ya que los pacientes tienen una evolución posiblemente letal a pesar del diagnóstico y tratamiento oportuno; 3 la tasa de mortalidad puede llegar hasta 30%. 2 Presentamos el caso de un niño diagnosticado de HCG-AHAI a los dos meses de edad, quien presentó una adecuada respuesta al tratamiento inmunosupresor.…”
Section: Wwwmedigraphicorgmxunclassified